Using solid‐state nuclear magnetic resonance to rationalize best efficiency of 2, 6‐dihydroxybenzoic acid over other 2, X‐dihydroxybenzoic acid isomers in solvent‐free matrix‐assisted laser desorption/ionization of poly(ethylene glycol). (2nd December 2020) - Pizzala, Hélène; Chendo, Christophe; Charles, Laurence
Abstract : Rationale: Among isomers of dihydroxybenzoic acid (DHB), 2, 5‐DHB is often the most efficient matrix in matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS) for a great variety of compounds. Yet, when performing solvent‐free MALDI, 2, 6‐DHB yields better results for poly(ethylene glycol [PEG]). This intriguing feature is explored here using solid‐state nuclear magnetic resonance (NMR). Methods: Ternary mixtures were prepared by grinding 2, X ‐DHB ( X = 3–6), poly(ethylene glycol) ( M n = 2000 g mol −1 ) and lithium fluoride (LiF) in a matrix/analyte/salt molar ratio of 50/1/10 for 16 min under a controlled atmosphere. After mixing, a few grains were applied to the MALDI target for MS analysis, whereas the major part of the ground sample was transferred into rotors to perform 13 C, 7 Li, and 19 F NMR experiments. Results: Lithiated PEG chains are mainly formed with 2, 6‐DHB in solvent‐free MALDI, but their abundance increases with 2, 3‐DHB and 2, 4‐DHB when water uptake is favored by a humid atmosphere. Solid‐state NMR shows that grinding 2, 6‐DHB‐based samples in atmospheric conditions leads to a solid phase in which the matrix, PEG, and salt molecules exhibit a high mobility compared with systems involving other 2, X ‐DHB isomers. This mobile environment would favor (as a solvent) LiF dissociation and best promote PEG cationization. Conclusions: Complementary data in 13 C, 7 Li, and 19 F NMR spectra are consistent with the formation of a solid phase of high mobility composed of 2, 6‐DHB, PEG, and the two salt components that ultimately favor the production of lithiated PEG chains.